Analisis Faktor-Faktor Yang Mempengaruhi Impor Beras Di Sumatera Utara - Sinta Rahmawati; Noni Rozaini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The study aims to identify and analyze factors that influence rice imports in North Sumatra. The type of data used in this study is secondary data. Secondary data is a source of research data obtained by researchers indirectly through intermediary media. Secondary data is generally evidence, records or historical reports that have been compiled in published archives and that have not been published. After the data is collected, the data analysis will be carried out using a computer device through the Eviews application program version 9. The analysis of the data was carried out to determine the extent to which the free variables (X1) Rice Production (X2) Rice Price, (X3) Rice Consumption and (Y) Rice Import were determined by using the regression model Error Correlation Model (ECM) to know the effects of the variables in the long and short term. The results of ECM analysis or the results of the short-term analysis of variables of production and rice prices have a negative and significant impact on rice imports, while the variable of rice consumption has a positive and non-significant impact on imports of rice in North Sumatra.